The International Aspects of the Smuggling of Migrants Across State Borders and the Fight Against it - Mamuka Egutidze (European Scientific Journal, ESJ, 2022)
This paper focuses on highlighting the international aspects of the smuggling of migrants across state borders and the fight against it. The relevance of the issue is due to chaotic migration in the process of globalization, the intensification of the illegal movement of migrants across the state border by transnational organized criminal groups, the danger of a merger of migrants and human trafficking, as well as criminal coincidence of migration and terrorism. Historical, statistical, normative-logical comparisons, and a number of other methodologies were utilized in the study. The legal attitude of individual states towards the smuggling of migrants across the state border and the compliance of this attitude with the United Nations conventions and their complementary protocols are also presented in this study.